Infective endocarditis caused by Streptococcus mutans. Issue 4 (April 1977) - McGhie, D; Hutchison, J G; Nye, F; Ball, A P
Abstract : Members of the viridans group of streptococci are the commonest causes of bacterial endocarditis. However, Streptococcus mutans, a member of this group associated with dental caries which might be expected to be commonly associated with endocarditis, has only rarely been reported. This is possibly because of difficulties in isolation and identification. Differing blood culture media may affect the chances of isolation of these organisms, and, though brain-heart infusion, thiol, tryptic soy, and glucose-brain infusion broths have all proved satisfactory, subcultures may require increased CO2 concentrations for growth. Plemorphism in the resultant colonies and in the individual organisms may give rise to a hazardous misinterpretation of this appearance as contamination. Strep. mutans and the similarly penicillin sensitive Strep. bovis may be differentiated from the penicillin resistant enterococci by their lincomycin sensitivity and intolerance of 6-3 per cent sodium chloride. Precise differentiation of streptococci in bacterial endocarditis is of value both epidemiologically and in the management of the disease.